Evaluation of ASEAN NCAP’s Adult Occupant Protection on Body Region using Analytical Hierarchy Process - Ezrin Hani, Sukadarin; Hanida, Abdul Aziz; Nurud Suria, Suhaimi; Hairunnisa, Osman; Mimi Nabila, Mohd Noordin; Ikram, Shafie (Society of Automotive Engineers Malaysia, 2020)
Global efforts in reducing road accidents were lead to the existence of a new car assessment program to ensure that the produced car may give life protection from traumatic death or injuries. Adult Occupant Protection (AOP), Child Occupant Protection (COP) and Safety Assist Technology (SAT) are domains used for the New Car Assessment Program for Southeast Asian Countries (ASEAN NCAP). Focusing on AOP domain, it is contributing for 50% of the overall rating system of ASEAN NCAP with a maximum 36 points from three main assessments: (1) offset frontal test (OFT), (2) side impact test (SIT) and (3) head protection technology (HPT). However, for this study, only OFT and SIT assessments are focused. Knowing that ASEAN NCAP is struggling to provide an accurate assessment of every new car evaluation. However, it is also important to ensure that the accurate assessment stays relevant. So, to what extend OFT and SIT may be giving protection to the car driver and passenger if there is any collision, need to be explored. Therefore, experts from various related industries were gathered in one expert panel meeting to brainstorm and discuss how OFT and SIT work and how robust they can be giving protection when an accident happens. Analytical Hierarchy Process (AHP) is used to analyse the experts’ input. Based on the finding, it is proved that the ASEAN NCAP assessment for AOP with considering OFT and SIT assessments were well developed and suitable to the current needs. In the future, cars on the road will become safer due to every party response to the ASEAN NCAP initiative positively.